The Impact of Economic Fluctuations on Project Management Practices in Large-Scale Construction Projects - Wasif Ali Khan (iRASD Journal of Management)
This study investigates the influence of economic changes on management practices in Pakistan, focusing on key areas, including budgeting, cost management, monitoring, project planning, resource allocation, procurement, and risk management. Surveys were conducted to obtain data from 150 project managers in various sectors in Karachi. The results suggest that economic changes substantially impact management's decision-making process in Pakistan's firms. Managers respond to economic instability by implementing adaptive actions such as modifying budgets, strengthening cost controls, improving monitoring systems, revising project plans, reallocating resources, refining procurement methods, and strengthening risk management frameworks. These insights suggest that organizational resilience can be improved by implementing better planning, enhancing risk management practices, optimizing budgeting and cost management, strengthening monitoring and control mechanisms, refining resource allocation and procurement strategies, and fostering organizational agility.